Planning and Implementation of Bicycle Paths Connecting Colleges and Government Offices in Bengkalis Island - Sastra, Marhadi; Lisya, Mutia (Politeknik Negeri Bengkalis, 2024)
Environmentally friendly mobility is an urgent need for developing areas, including Bengkalis Island. The planning anddevelopment of bicycle paths as a connection between colleges and local government offices on Bengkalis Island consider factorsof efficiency, safety, and comfort. This bicycle path planning is also expected to support a healthy lifestyle and reduce pollutionand traffic congestion. This research uses a qualitative descriptive approach with mapping analysis and community needssurveys. The research results show that bicycle paths are not only beneficial for students and employees but also become part ofthe environmentally friendly infrastructure for the wider community. Based on the survey results, it is evident that the communitypredominantly desires the presence of bicycle paths. After conducting a road inventory, it was found that the accessible road thatcan be planned for the bicycle path is from Pramuka Road to the Polytechnic State Campus of Bengkalis and the road connectingto the Bengkalis government offices, while other roads have not yet provided sufficient width. The planned bicycle path willadhere to the circular letter from the Ministry of Public Works, Directorate General of Highways No. 05/SE/Db/2021 regardingBicycle Facility Design.